Assessment of the Level of Groundwater Vulnerability to Pollution Using the DRASTIC Methodin Jogoroto District, Jombang Regency - Alfaridzi, Em Rafif Sultan; Siswoyo, Hari; Sayekti, Rini Wahyu (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
There are more than 70 small tofu factories in the Jogoroto District, which generate a large amount of liquid waste from tofu processing that has not been treated optimally. This certainly creates a potential for the waste to contaminate groundwater in the Jogoroto District. The assessment of groundwater vulnerability to contamination can be conducted using the DRASTIC method, which involves 7 parameters.In this study, there are 24 dug well points spread across the entire Jogoroto District, which were monitored periodically over a 5-month period, from July 2023 to November 2023. Based on the resulting groundwater vulnerability distribution map, laboratory tests on groundwater quality were carried out, using parameters from the Minister of Health Regulation No. 2 of 2023 concerning clean water and the Minister of Environment Regulation No. 5 of 2014 on effluent quality standards.The study found that the DRASTIC index value during the research period ranged from 140 to 212, with three levels of vulnerability: moderate, high, and very high. The high vulnerability level dominated the study area. However, based on the validation results, it was found that the groundwater quality in the Jogoroto District, Jombang Regency, is not contaminated.